PENGEMBANGAN MEDIA KAPOMEL (KOTAK POHON MELEDAK) BERBASIS ALUR MERDEKA BELAJAR MATA PELAJARAN IPAS - Amalia Dwi Cahyani; Ariga Bahrodin (Jurnal Bionatural, 2024)
Interesting learning for students cannot be separated from the innovation or creativity of educators in implementing the learning process in the classroom. One innovation that is often carried out is implementing learning using learning media. Learning media is able to attract students' imagination and concentration in understanding material. In realizing the independent flow, it can be dedicated to project-based learning for educators and students. Therefore, researchers want to carry out research and development of KAPOMEL (Exploding Tree Box) media based on the independent learning flow. The research was conducted on 27 class IV-A students at MI Rahmad Said Peterongan Jombang with the aim of describing the development of the KAPOMEL (Exploding Tree Box) media based on the independent flow of learning in the Natural and Social Sciences (IPAS) class IV-A subjects and analyzing the feasibility of the KAPOMEL media according to expert validators. The ADDIE development model chosen in this research consists of the analysis stage, design stage, development stage, implementation stage and evaluation stage. The data obtained is in the form of qualitative and quantitative data obtained from the output of the validators and then analyzed using descriptive statistics. The percentage obtained from media experts reached 76%, material experts 96% and learning experts 100% with an average of 90%, which means that the KAPOMEL (Exploding Tree Box) media based on the independent flow of learning in class IV science subjects at MI Rahmad Said Peterongan Jombang is very proper to use.